Estructura monoparental de cinco familias representadas por el padre en la ciudad de Bogotá (2019)
The reader will be able to find the structural characteristics of five single-parent families in Bogotá, with a father figure, seen from the hierarchy, roles and communication and, phenomenologically, the operations based on interactions. In the paternal-filial single-parent family structure it was found that families move away from the established scheme within traditional culture, they are unconventional families, in which the male and female roles converge in the men, remaining as the only parental figure that he may well assume from care, or he may fall into parentalization; specific topics about this particular structure are described, they were organized based on the responses expressed by the parents in the indepth interview, which was used as an information gathering technique.